A numerical solving method using the parallel computing technologies for the quantum-kinetic models. Issue 5 (May 2019) - Abramov, G V; Gavrilov, A N; Akinina, Ju S
Abstract: In the process of designing a carbon nanostructure (CNS) synthesis system, the main task is to determine the technological and functional parameters of synthesis. We offered a mathematical model of the process for the purpose of studying the synthesis processes using the graphite thermal evaporation, based on the Boltzmann kinetic equation, which takes into account elastic and non-elastic particle interactions. We offer a numerical solving method using the parallel computing technologies. We conducted the study of the effect of the main synthesis parameters on the carbon cluster formation and the amount of obtained material containing CNS.